Structural analysis of β‐L‐arabinobiose‐binding protein in the metabolic pathway of hydroxyproline‐rich glycoproteins in Bifidobacterium longum. (17th April 2020) - Miyake, Masayuki; Terada, Tohru; Shimokawa, Michiko; Sugimoto, Naohisa; Arakawa, Takatoshi; Shimizu, Kentaro; Igarashi, Kiyohiko; Fujita, Kiyotaka; Fushinobu, Shinya
Abstract : Bifidobacterium longum is a symbiotic human gut bacterium that has a degradation system for β‐arabinooligosaccharides, which are present in the hydroxyproline‐rich glycoproteins of edible plants. Whereas microbial degradation systems for α‐linked arabinofuranosyl carbohydrates have been extensively studied, little is understood about the degradation systems targeting β‐linked arabinofuranosyl carbohydrates. We functionally and structurally analyzed a substrate‐binding protein (SBP) of a putative ABC transporter (BLLJ_0208) in the β‐arabinooligosaccharide degradation system. Thermal shift assays and isothermal titration calorimetry revealed that the SBP specifically bound Ara f ‐β1, 2‐Ara f (β‐Ara2 ) with a K d of 0.150 μm, but did not bind L‐arabinose or methyl‐β‐Ara2 . Therefore, the SBP was termed β‐arabinobiose‐binding protein (BABP). Crystal structures of BABP complexed with β‐Ara2 were determined at resolutions of up to 1.78 Å. The findings showed that β‐Ara2 was bound to BABP within a short tunnel between two lobes as an α‐anomeric form at its reducing end. BABP forms extensive interactions with β‐Ara2, and its binding mode was unique among SBPs. A molecular dynamics simulation revealed that the closed conformation of substrate‐bound BABP is stable, whereas substrate‐free form can adopt a fully open and two distinct semi‐open states. The importer system specific for β‐Ara2 may contribute to microbial survival in biological niches with limited amounts of digestible carbohydrates. Database: Atomic coordinates and structure factors (codes 6LCE and 6LCF) have been deposited in the Protein Data Bank (http://wwpdb.org/ ). Abstract : A symbiotic human gut bacterium, Bifidobacterium longum, has a degradation system for β‐arabinooligosaccharides, which are present in the hydroxyproline‐rich glycoproteins of edible plants. The crystal structure of β‐arabinobiose‐binding protein (BABP) was determined. BABP specifically bound Ara f ‐β1, 2‐Ara f with a K d of 0.150 μm as revealed by ITC measurement. A molecular dynamics simulation revealed that substrate‐free BABP adopts a fully open and two distinct semi‐open states.